Pain and social decision-making: New insights from the social framing effect. Issue 4 (December 2019) - Gu, Ruolei; Liu, Jie; Cui, Fang
This paper focuses on the social function of painful experience as revealed by recent studies on social decision-making. Observing others suffering from physical pain evokes empathic reactions that can lead to prosocial behavior (e.g., helping others at a cost to oneself), which might be regarded as the social value of pain derived from evolution. Feelings of guilt may also be elicited when one takes responsibility for another's pain. These social emotions play a significant role in various cognitive processes and may affect behavioral preferences. In addition, the influence of others' pain on decision-making is highly sensitive to social context. Combining neuroimaging techniques with a novel decision paradigm, we found that when asking participants to trade-off personal benefits against providing help to other people, verbally describing the causal relationship between their decision and other people's pain (i.e., framing) significantly changed participants' preferences. This social framing effect was associated with neural activation in the temporoparietal junction (TPJ), which is a brain area that is important in social cognition and in social emotions. Further, transcranial direct current stimulation (tDCS) on this region successfully modulated the magnitude of the social framing effect. These findings add to the knowledge about the role of perception of others' pain in our social life.